Combined calculation of radiation from large-sized ground RW storage facilities on the basis of Monte Carlo method - Rudychev, V.G.; Azarenkov, N.A.; Girka, I.O.; Rudychev, D.V.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2019)
A technique to reduce the dose rates, produced by large-sized ground-based radiation sources with dozens of radiating elements of the same geometry arranged along the perimeter, is developed. The radiating elements represent the concrete rectangular casks into which cylindrical barrels filled with compacted RW are loaded. The spatial distribution of the radiation around the cask is calculated by the Monte Carlo method. The radiation is assumed to be produced by the definite radionuclides of RW. Shielding by neighboring containers and the presence of an additional biological shielding are taken into account. Different options of the container arrangement are considered.